1978
DOI: 10.1029/gl005i002p00127
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam injection experiments: The beam‐plasma discharge at low pressures and magnetic field strengths

Abstract: Abslract. A column of enhanced density plasma,exceeding the density expected from ionization by primary beam electrons, has been observed in a large vacuum system at low magnetic fields (1 to 1.5 G) and low ambient pressures (10 -6 to 10 -s torr). The peak luminosity of the discharge is about 10 times that of the beam alone, with a radius increase by a factor of 3. In the absence of the discharge, RF emission is observed at 1.1 to 1.2 fc-A strong band of RF noise with upper frequency cutoff at about fc is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…Lab studies of BPD at the NASA/JSC chamber have been conducted for some time (Bernstein-et al, 1978). These investigations have shown that the radio frequency waves above 1 MHz may not be large enough in amplitude to provide the necessary energization for BPD (Bernstein and Kellogg, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Lab studies of BPD at the NASA/JSC chamber have been conducted for some time (Bernstein-et al, 1978). These investigations have shown that the radio frequency waves above 1 MHz may not be large enough in amplitude to provide the necessary energization for BPD (Bernstein and Kellogg, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…This critical current level yields a marked increase in ion-pair-production, a greatly enhanced 3914 X emission, a modification of the primary beam velocity distribution and the emission of intense RF waves. The BPD has been the subject of a continuing series of space-simulation experiments (Bernstein et al, 1978;Bernstein et al, 1980and Jost et al, 1981) One such recent work (Walker et al, 1981) has determined that the density-related plasma condition for BPD threshold +1.3 can be expressed as w = (5.8 -1.9 ) Wc, where (w ,w ) are p -1 9p…”
Section: Manuscript Submitted April 30 1981mentioning
confidence: 99%
“…One of the areas in space-related beam-plasma interactions to receive considerable attention in recent years has been the collective plasma process called the beam-plasma-discharge (Bernstein et al, 1978;Bernstein et al, 1980;and Jost et al, 1981).…”
Section: Manuscript Submitted April 30 1981mentioning
confidence: 99%
“…The Beam-Plasma-Discharge (BPD) instability (Getty and Smullin, 1963) has re-emerged in recent years (Smullin, 1981;Bernstein et al, 1978) as a fundamental process to be considered by designers of space vehicle-borne electron accelerator experiments. Because of concerns over vehicle neutralization during these experiments and an interest in further understanding of the BPD process (Cambou, 1975(Cambou, , 1978) a series of space simulation investigations of the BPD phenomenon was undertaken in the large vacuum chamber facility at…”
Section: Introductionmentioning
confidence: 99%
“…Johnson Space Center (Bernstein 1978(Bernstein , 1979Szuszczewicz 1979Szuszczewicz , 1982aPapadopoulos, 1982;Anderson, 1981 where VB is the beam energy in volts, B the magnetic field in gauss, P the ambient neutral particle pressure in torr, and L the beam length in meters.…”
Section: Introductionmentioning
confidence: 99%